Nghiên cứu lí thuyết sự tạo sản phẩm OH•, NH2•, HCN, H2O, CS và HNO từ phản ứng của axit fulminic với gốc mercapto (HCNO+HS•) - Nghĩa, Nguyễn Trọng; Minh Huệ, Nguyễn Thị; Thu Ngọc, Phan Thị (Vietnam Journal of Chemistry, 2014)
The mechanism for the reaction of the HS radical with fulminic acid (HCNO) to gain OH·, NH2·, HCN, H2O, CS and HNO has been investigated at the B3LYP/6-311++G(3df,2p) level of theory. The potential energy surface (PES) for this system shows that there are eight different product pathways: PR1 (SCO +NH2·), PR2 (HSCN + OH·), PR3 (SCN· + H2O), PR4 (CS + NHOH·), PR5 (SCNH + OH·), PR6 (HCS· + HNO), PR7 (CS + NH2O·) and PR8 (HCN + HSO·). The results indicate that PR2 (HSCN + OH·), PR3 (SCN· + H2O) are the major product channels with minor contributions from PR4 (CS + NHOH·), PR5 (SCNH + OH·), and PR8 (HCN + HSO·) whereas the other channels for PR1 (SCO +NH2·), PR6 (HCS· + HNO), PR7 (CS + NH2O·) are less favorable. Keywords: Reaction mechanism, HS· radical, forming OH·, fulminic acid HCNO, potential energy surface (PES).